KEBERFUNGSIAN KELUARGA ANAK KORBAN EKSPLOITASI DI LAMPU MERAH MALL SKA PEKANBARU - Fuada, Nurul; Umari, Tri; Putra, Roby Maiva (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The purpose of this study is to describe the profile of the functions of families and children of victims of exploitation in the Red Light Mall SKA in terms of the identity of children of victims of exploitation, psychological conditions of children of victims of exploitation, family integrity, and social relations in families at the Red Light at SKA Mall. This study, in January 2020, used a Qualitative approach, with a descriptive type of research. Based on the results of research that has been described and discussed regarding the family functions of children victims of exploitation in SKA Pekanbaru, Mall red light, which involves 8 children and 3 parents. The family profile of children of victims of exploitation, out of 8 children who studied psychological conditions and family integrity, 7 of them were fine. In the functioning of the families of children of victims of exploitation, of the 8 children discovered by the researchers, none of them actually performed the functions of the whole family. Although a normal family can carry out all its functions correctly. If one function is not carried out, it will create a family that is not functioning or an abnormal family. And this will inhibit the pattern of child development later.Key Words: Family Functioning, Child Victims of Exploitation